Associations between baseline biomarkers and lung function in HIV-positive individuals. (15th March 2019) - MacDonald, David M.; Zanotto, Alexander D.; Collins, Gary; Baker, Jason V.; Czarnecki, Marcin; Loiza, Eliana; Nixon, Daniel E.; Papastamopoulos, Vasileios; Wendt, Chris H.; Wood, Robin; Kunisaki, Ken M.
Abstract : Objective: The aim of this study was to analyse the association of baseline biomarker data with cross-sectional lung function and subsequent decline in lung function in HIV-positive persons. Design: Lung function was modelled in all START pulmonary substudy participants who had baseline biomarker data and good-quality spirometry. In longitudinal analyses, we restricted to those participants with at least one good-quality follow-up spirometry test. Methods: We performed linear regression of baseline forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and FEV1 /FVC and their longitudinal slopes on log2 -transformed baseline biomarkers with adjustment for age, sex, race, region, smoking status, baseline CD4 + T-cell counts and baseline HIV-RNA. Biomarkers included D-dimer, high-sensitivity C-reactive protein (hsCRP), interleukin (IL)-6, IL-27, serum amyloid A, soluble intercellular adhesion molecule (sICAM)-1, soluble vascular cell adhesion molecule (sVCAM)-1, albumin and total bilirubin. Results: Among 903 included participants, baseline median age was 36 years, CD4 + cell count was 647 cells/μl, and 28.5% were current smokers. In adjusted analyses, elevated markers of systemic inflammation (hsCRP, IL-6 and serum amyloid A) were associated with lower baseline FEV1 and FVC. Elevated D-dimer and IL-6 were associated with worse airflow obstruction (lower FEV1 /FVC). Despite these cross-sectional associations at baseline, no associations were found between baseline biomarkers and subsequent longitudinal lung function decline over a median follow-up time of 3.9 years (3293 spirometry-years of follow-up). Conclusion: Commonly available biomarkers, in particular markers of systemic inflammation, are associated with worse cross-sectional lung function, but do not associate with subsequent lung function decline among HIV-positive persons with early HIV infection and baseline CD4 + T-cell counts more than 500 cells/μl. Abstract : Supplemental Digital Content is available in the text